A generalization of an extended stochastic integral - Berezansky, Yu. M.; Tesko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We propose a generalization of an extended stochastic integral to the case of integration with respect to a broad class of random processes. In particular, we obtain conditions for the coincidence of the considered integral with the classical Itô stochastic integral.